Clinical and epidemiological features of chronic Trypanosoma cruzi infection in patients with HIV/AIDS in Buenos Aires, Argentina - Benchetrit, Andres Guillermo (2018)
Objectives: Trypanosoma cruzi reactivation in HIV patients is considered an opportunistic infection, usually with a fatal outcome. The aim of this study was to describe the epidemiological and clinical features of T. cruzi infection in HIV patients and to compare these findings between patients with and without Chagas disease reactivation. Methods: The medical records of T. cruzi–HIV co-infected patients treated at the Muñiz Infectious Diseases Hospital from January 2005 to December 2014 were reviewed retrospectively. Epidemiological and clinical features were assessed and compared between patients with and without Chagas disease reactivation. Results: The medical records of 80 T. cruzi–HIV co-infected patients were reviewed. The most likely route of T. cruzi infection was vector-borne (32/80 patients), followed by intravenous drug use (12/80). Nine of 80 patients had reactivation. Patients without reactivation had a significantly higher CD4 T-cell count at diagnosis of T. cruzi infection (144 cells/μl vs. 30 cells/μl, p = 0.026). Chagas disease serology was negative in two of nine patients with reactivation. Conclusions: Serological assays for T. cruzi infection may be negative in severely immunocompromised patients. Direct parasitological techniques should be performed in the diagnosis of patients for whom there is a suspicion of T. cruzi reactivation. HIV patients with a lower CD4 count are at higher risk of reactivation.